PENGARUH KEPEMIMPINAN, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA (Studi Pada Kantor Wilayah BPJS Ketenagakerjaan Jateng & DIY) - INDRI YANTI, 14.05.51.0255 (Students' Journal of Economic and Management, 2018)
This study aims to determine and analyze the influence of leadership, work discipline, and work environment on job satisfaction at the Central Java & DIY BPJS Regional Office. The population in this study were all employees of the Central Java & DIY BPJS Regional Office which amounted to 50 respondents with their spread using saturated census or sampling methods. In the data analysis using this validity test measured by Pearson correlation which states all valid variables, reliability testing using Cronbach alpha which states all variables are reliable, test the coefficient of determination using the adjusted R Square which shows the independent variable is able to explain variations in changes to the independent variables of 45 , 4%, F test using a 5% significance level which states that there is a simultaneous influence of the independent variable on the dependent variable, multiple linear regression test using standardized coefficients which shows leadership influence on job satisfaction by 0.244, work discipline affects job satisfaction by 0.305 and the work environment has an effect on job satisfaction of 0.318, and the t test by using a significance level of 5%, which shows leadership with a significance of 0.046 which proves the hypothesis is accepted, work discipline with significance amounting to 0.0024 which proves the hypothesis is accepted, and the work environment with a significance of 0.026 which proves the hypothesis is accepted. It can be concluded that the variables of leadership, work discipline, and work environment affect job satisfaction. Keyword : leadership, work discipline, work environment, job satisfaction